Articulation or phonology? Evidence from longitudinal error data. (2nd November 2018) - Dodd, Barbara; Reilly, Sheena; Ttofari Eecen, Kyriaki; Morgan, Angela T.
ABSTRACT: Children's speech difficulties can be motor (phone misarticulation) or linguistic (impaired knowledge of phonological contrasts and constraints). These two difficulties sometimes co-occur. This paper reports longitudinal data from the Early Language in Victoria Study (ELVS) at 4 and 7 years of age. Of 1494 participants, 93 made non-age appropriate speech errors on standardised assessments at 4 years, and were able to be reassessed at 7 years. At 4 years, 85% of these children only made phonological errors, 14% made both articulation and phonological errors and one child only made articulation errors (a lateral lisp). In total, 8 of 13 children making both articulation and phonological errors at 4 years had resolved by 7 years. Unexpectedly, eight children who had demonstrated articulation of fricatives at 4 years, acquired distorted production of ≥ 50% of occurrences of/s, z/ by 7 years. In total, then, 22 children (24% of children with speech difficulties) made articulatory errors at one or both assessments. Case data for all children are presented. Theoretical and clinical implications are considered.